196k views
5 votes
Find the average rate

Find the average rate-example-1
User Seanb
by
5.3k points

1 Answer

3 votes

Answer:

5

Explanation:

To find the average rate of change of the function between two points
x_1, x_2, we can use the following formula:


m=(f(x_2)-f(x_1))/(x_2-x_1)

The function in this problem is


f(x)=x^2-2x+9

At
x_1 = 1, we have


f(x_1)=f(1)=1^2-2(1)+9=8

At
x_2 = 6, we have


f(x_2) = f(6) = 6^2-2(6)+9=33

So now we can apply the first formulat to find the average rate of change of the function between the two points:


m=(33-8)/(6-1)=(25)/(5)=5

User Peter Mugendi
by
6.2k points